Predicting the impacts of anthropogenic disturbances on marine populations. Issue 5 (7th May 2018) - Nabe‐Nielsen, Jacob; van Beest, Floris M; Grimm, Volker; Sibly, Richard M; Teilmann, Jonas; Thompson, Paul M
Abstract: Marine ecosystems are increasingly exposed to anthropogenic disturbances that cause animals to change behavior and move away from potential foraging grounds. Here we present a process‐based modeling framework for assessing population consequences of such sub‐lethal behavioral effects. It builds directly on how disturbances influence animal movements, foraging and energetics, and is therefore applicable to a wide range of species. To demonstrate the model we assess the impact of wind farm construction noise on the North Sea harbor porpoise population. Subsequently, we demonstrate how the model can be used to minimize population impacts of disturbances through spatial planning. Population models that build on the fundamental processes that determine animal fitness have a high predictive power in novel environments, making them ideal for marine management.